If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(7x + -4) = lm(2x + 11) Reorder the terms: ln(-4 + 7x) = lm(2x + 11) (-4 * ln + 7x * ln) = lm(2x + 11) (-4ln + 7lnx) = lm(2x + 11) Reorder the terms: -4ln + 7lnx = lm(11 + 2x) -4ln + 7lnx = (11 * lm + 2x * lm) -4ln + 7lnx = (11lm + 2lmx) Solving -4ln + 7lnx = 11lm + 2lmx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-11lm' to each side of the equation. -4ln + -11lm + 7lnx = 11lm + -11lm + 2lmx Reorder the terms: -11lm + -4ln + 7lnx = 11lm + -11lm + 2lmx Combine like terms: 11lm + -11lm = 0 -11lm + -4ln + 7lnx = 0 + 2lmx -11lm + -4ln + 7lnx = 2lmx Add '-2lmx' to each side of the equation. -11lm + -4ln + -2lmx + 7lnx = 2lmx + -2lmx Reorder the terms: -11lm + -2lmx + -4ln + 7lnx = 2lmx + -2lmx Combine like terms: 2lmx + -2lmx = 0 -11lm + -2lmx + -4ln + 7lnx = 0 Factor out the Greatest Common Factor (GCF), 'l'. l(-11m + -2mx + -4n + 7nx) = 0Subproblem 1
Set the factor 'l' equal to zero and attempt to solve: Simplifying l = 0 Solving l = 0 Move all terms containing l to the left, all other terms to the right. Simplifying l = 0Subproblem 2
Set the factor '(-11m + -2mx + -4n + 7nx)' equal to zero and attempt to solve: Simplifying -11m + -2mx + -4n + 7nx = 0 Solving -11m + -2mx + -4n + 7nx = 0 Move all terms containing l to the left, all other terms to the right. Add '11m' to each side of the equation. -11m + -2mx + -4n + 11m + 7nx = 0 + 11m Reorder the terms: -11m + 11m + -2mx + -4n + 7nx = 0 + 11m Combine like terms: -11m + 11m = 0 0 + -2mx + -4n + 7nx = 0 + 11m -2mx + -4n + 7nx = 0 + 11m Remove the zero: -2mx + -4n + 7nx = 11m Add '2mx' to each side of the equation. -2mx + -4n + 2mx + 7nx = 11m + 2mx Reorder the terms: -2mx + 2mx + -4n + 7nx = 11m + 2mx Combine like terms: -2mx + 2mx = 0 0 + -4n + 7nx = 11m + 2mx -4n + 7nx = 11m + 2mx Add '4n' to each side of the equation. -4n + 4n + 7nx = 11m + 2mx + 4n Combine like terms: -4n + 4n = 0 0 + 7nx = 11m + 2mx + 4n 7nx = 11m + 2mx + 4n Add '-7nx' to each side of the equation. 7nx + -7nx = 11m + 2mx + 4n + -7nx Combine like terms: 7nx + -7nx = 0 0 = 11m + 2mx + 4n + -7nx Simplifying 0 = 11m + 2mx + 4n + -7nx The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
l = {0}
| 3x^3+7x^2+4x= | | 0.2(p+4)-0.7(p+2)=-3 | | 27x+21= | | (5x^2-30)/150x=1/6 | | a=22/7x45/2² | | 10-8(3-s)+5(s+3)=30 | | 30x^2-38x+12=0 | | 22/7(45/2)² | | X+3=(X-1)*2 | | 7y-25=-33+6y | | 20x^2-11-4= | | 4n^2-39+95=0 | | 5y-14=-22+y | | 3(q-3)+4q-1=5q+5+2q | | X^2+2ax=b | | -51=7(-1+6p)-6(7+7p) | | 3m+7+3(3m-4)-4(m+4)=0 | | 100=1/2*5t^2 | | 100=1/2(5)t^2 | | d=8sin(6) | | 8x^3+27x^2+12x-11=0 | | x^2-9y^2-4x-18y-14=0 | | 2b^2+16b+35=0 | | 3/4y=32 | | 1+1+x=15891769817369875983457193761439856813945619865198365190645 | | 0.17y+0.07(y+7000)=1450 | | 9/14-10/21 | | 16x^2+15x-35=0 | | Y-3/5=1/2 | | 10x^6/5-5x^1/5 | | 6x-6z=6+5y | | 10(-2x+1)=-14(x+2)+39-6x |